Bahasa Inggris - Widya Mardiyanti Domili; Laksmyn Kadir; Wiharsri (Journal of Health, Technology and Science (JHTS), 2020)
This study aims to determine the results of urine nitrite examination in patients with Urinary Tract Infection (UTI) as well as to determine the factors that influence it. The method in this study uses a descriptive quantitative approach. The type of data used is primary data in the form of research results and secondary data in the form of data from literature, books and documents. The sampling technique in this study used a purposive sampling technique, with a sample of 30 people.The results showed that of the 30 patients diagnosed with UTI, 19 people or 63.3% had positive urine nitrite, while 11 people had negative urine nitrite or 36.7%. Factors that affect urine nitrite levels in patients with Urinary Tract Infection (UTI) are individual hygiene, use of catheters, and gender. UTI sufferers are more common in women than men.